Proto-maya y lingüística diacrónica. Una (breve y necesaria) introducción - José Andrés Alonso de la Fuente (Journal de la Société des Américanistes)
Proto-Mayan and diachronic linguistics. A (brief and necessary) introduction. The goal of this paper is to underline the importance of the diachronic linguistics and the possibilities which it offers from the interdisciplinary perspective. The co-operation with archaeology and history seems to be specially productive and successful, as it will be show here. In addition, the Mayan case is exceptional, in fact unique among the American native languages, because of its old written records, as well as the richness of documents during the Colonial times.